2016
DOI: 10.3390/s16030347
|View full text |Cite
|
Sign up to set email alerts
|

Standalone GPS L1 C/A Receiver for Lunar Missions

Abstract: Global Navigation Satellite Systems (GNSSs) were originally introduced to provide positioning and timing services for terrestrial Earth users. However, space users increasingly rely on GNSS for spacecraft navigation and other science applications at several different altitudes from the Earth surface, in Low Earth Orbit (LEO), Medium Earth Orbit (MEO), Geostationary Earth Orbit (GEO), and feasibility studies have proved that GNSS signals can even be tracked at Moon altitude. Despite this, space remains a challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…These studies assumed that all signals in the considered GPS antenna sidelobes can be used for navigation as demonstrated with in-orbit measurements in [10]. The results shown in Figure 3, which shows the same results obtained in Figure 5 of [7], have revealed that, by assuming a 0-dBi receiver antenna gain, the fourth strongest GPS L1 C/A signal (at least four ranges are required to compute the 3D position) at receiver antenna never goes below a power level of À168.5 dBm, neglecting a few lower peaks. Therefore, a very high sensitivity receiver architecture is required.…”
Section: Gps Signal Characteristicssupporting
confidence: 58%
See 4 more Smart Citations
“…These studies assumed that all signals in the considered GPS antenna sidelobes can be used for navigation as demonstrated with in-orbit measurements in [10]. The results shown in Figure 3, which shows the same results obtained in Figure 5 of [7], have revealed that, by assuming a 0-dBi receiver antenna gain, the fourth strongest GPS L1 C/A signal (at least four ranges are required to compute the 3D position) at receiver antenna never goes below a power level of À168.5 dBm, neglecting a few lower peaks. Therefore, a very high sensitivity receiver architecture is required.…”
Section: Gps Signal Characteristicssupporting
confidence: 58%
“…Note that the term "altitude" here always refers to the distance of the receiver from Earth's surface. As illustrated in Figures 5 and 6 (and equivalently in figures 6 and 7 of [7]), the analysis of the dynamics has shown that the carrier frequency can be affected by Doppler shifts and Doppler rates of up to 20 kHz and up to 3 Hz/s, respectively, at the Moon altitude (when the signals are weaker) and of up to 60 kHz and up to 65 Hz/s at the very beginning of the MTO (when the signals are stronger). Note that the spikes at the beginning of the orbit (of up to 60 kHz and up to 65 Hz/s) are due to the very high velocity of the receiver at the perigee of the MTO.…”
Section: Gps Signal Characteristicsmentioning
confidence: 80%
See 3 more Smart Citations